2020
DOI: 10.3389/fchem.2020.00834
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Catalytic Properties of Supported and Encapsulated Gold Nanoparticles in Homocoupling Reactions

Abstract: This report describes strategies to increase the reactive surfaces of integrated gold nanoparticles (AuNPs) by employing two different types of host materials that do not possess strong electrostatic and/or covalent interactive forces. These composite particles are then utilized as highly reactive and recyclable quasi-homogeneous catalysts in a CC bond forming reaction. The use of mesoporous TiO 2 and poly(N-isopropylacrylamide), PNIPAM, particles allows for the formation of relatively small and large guest Au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Comparing AuNPs@MG-OH and AuNPs@MG-SH, AuNPs@MG-SH self-assembled by electrostatic interaction and Au−S bonding has better stability to facilitate the reduction smoothly, further improving the catalysis efficiency than that of AuNPs@MG-OH. 11,32,63,76,77 Competitiveness against Known PNIPAM-Based Materials. The catalytic performance of the AuNPs@MG-SH hybrid microgels (surface-covered) prepared in this study was compared with that of similar works according to the halflife (t 1/2 ), the mole ratio of Au and 4-NP, and the conversion of 4-NP.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Comparing AuNPs@MG-OH and AuNPs@MG-SH, AuNPs@MG-SH self-assembled by electrostatic interaction and Au−S bonding has better stability to facilitate the reduction smoothly, further improving the catalysis efficiency than that of AuNPs@MG-OH. 11,32,63,76,77 Competitiveness against Known PNIPAM-Based Materials. The catalytic performance of the AuNPs@MG-SH hybrid microgels (surface-covered) prepared in this study was compared with that of similar works according to the halflife (t 1/2 ), the mole ratio of Au and 4-NP, and the conversion of 4-NP.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…2b). 9,42 For polymer-Au nanocomposite (Fig. 2a), only a very small amount of PVP was added, and the AuNPs were embedded on the hydrophilic block of polymeric nano-spheres, leaving the relatively larger area of "naked" Au surface thus more accessible active sites.…”
Section: In Situ Synthesis Of Polymer-au Nanocompositementioning
confidence: 99%
“…citrate) in conventional metal nanoparticles often act as a physical barrier, which blocks the access of reactants during the reaction and adversely affects the overall catalytic performance. 8,9 By replacing the stabilizing/capping agents with polymeric nanoparticles, the surface of the metal nanoparticles is free from any capping agent barrier, thus it can serve as highly active catalysts. For polymer-metal nanocomposite, the metal nanoparticles are usually prepared in situ by reduction of a metal salt and immobilized on polymer based on the interaction between one of the polymer blocks and the metal ion.…”
Section: Introductionmentioning
confidence: 99%
“…Bae, Byun, and Kim et al prepared small and large Au NPs stabilized in mesoporous TiO 2 and poly(N-isopropylacrylamide) particles, respectively. These Au NPs exhibited a notably high catalytic activity in the homocoupling of phenylboronic acid, and interestingly, there was no obvious correlation between the apparent E a values and the size of Au NPs [160]. Dewan et al reported the first synthesis of a renewable, recyclable, environmental benign bio-nanocellulose-based honeycomb-like heterogeneous surface from waste pomegranate peel.…”
Section: Porous Materialsmentioning
confidence: 99%